(untitled) (Annals of Medical Research, 2021)
Aim: Tyrosine kinase inhibitors are a targeted and successful treatment modalities in the treatment of Chronic Myeloid Leukemia (CML). Imatinib mesylate is the most common of these inhibitors, but resistance reactions limit its use. It is believed that regulators in the Wnt signaling pathway play an important role in the treatment of CML. The aim of this study is to investigate possible expression changes of intracellular negative regulator genes after imatinib mesylate treatment in chronic myeloid leukemia cell line. Materials and Methods: Total RNA isolation was performed from K562 cells treated with Imatinib mesylate for 24 hours at 0.5 µM concentration and control native K562 cells. Following cDNA synthesis, expression changes of eight intracellular negative regulator genes were analyzed by Real-Time PCR. Results: When the results were evaluated, it was determined that the expression of 5 genes increased and the expression of 3 genes decreased in K562 cells treated with imatinib. Conclusion: When we suppressed Bcr-Abl with Imatinib in K562 cells, it was observed that there were changes in the expression levels of the intracellular negative regulator genes of the Wnt signaling pathway. These changes are important in defining new targets in CML treatment. To understand the roles of these negative regulators, it is important to conduct detailed research to develop new strategies for CML treatment.